Relation between antecedent rainfall or rainfall amount with the accurrence of landslide in universiti teknologi petronas - Mohd Arif bin Wan Mohd Dzulkifli, Mohd Arif (2009)
This study is presented to examine the relation between antecedent rainfall or rainfall amount with the occurrence of the landslide in Universiti Teknologi Petronas(UTP), Tronoh, Perak.